REVIEW: SCREENING PENYEBAB SCABIES - JUMADEWI, ASRI; SIMEULU, PUTRO (CENDEKIA: Jurnal Ilmu Pengetahuan, 2024)
Scabies is another name for scabies, which is caused by the flea/mite Sarcoptes scabiei var hominis, which is a class of parasites that can infest scabies. Symptoms include the appearance of pimples (papules), festering (pustules), followed by scratch marks (excoriation). Female fleas will place eggs in the layers of skin to form a tunnel (cuniculus), which is what causes intense itching at night. Bacteria can infect and complicate the occurrence of scabies due to secondary infestation. This disease is easily transmitted quickly, such as skin contact with the sufferer for a long time. The aim of this research is to determine the factors that can cause the infectious disease scabies (Sarcoptes scabiei). This research uses a literature review method through national journals for the last 10 years (2012-2023) with the keywords scabies, Sarcoptes scabiei, personal hygiene and santri. Search for review articles using web sources such as Google Scholar and other sources. The results of the review show that scabies sufferers are predominantly caused by personal hygiene behavior and environmental sanitation.. ABSTRAKKudis adalah nama lain scabies, yang disebabkan oleh jenis kutu/tungau Sarcoptes scabiei var hominis, yaitu golongan parasit yang dapat melakukan infestasi terhadap kejadian scabies. Gejala berupa munculnya bintil-bintil (papula), bernanah (pustula), diikuti adanya bekas garukan (ekskoriasi). Kutu betina akan menempatkan telur di dalam lapisan kulit hingga membentuk terowongan (kunikulus), inilah yang memacu rasa gatal hebat di malam hari. Bakteri dapat menginfeksi dan memperumit kejadiaan scabies akibat infestasi sekunder. Penyakit ini mudah menular dengan cepat, seperti kontak kulit dengan penderita dalam waktu yang lama. Tujuan penelitian ini untuk mengetahui faktor-faktor yang dapat menyebabkan penyakit menular scabies (Sarcoptes scabiei). Penelitian ini menggunakan metode literatur review melalui jurnal nasional pada 10 tahun terakhir (2012-2023) dengan kata kunci scabies, Sarcoptes scabiei, personal hygiene dan santri. Pencarian artikel review menggunakan sumber web seperti Google Scholar dan sumber lainnya. Hasil review menunjukkan bahwa penderita scabies dominan disebabkan oleh perilaku personal hygiene dan sanitasi lingkungan.